Triple Therapy for Socket Seal Surgery: A Case Report (Indian Journal of Case Reports, 2017)
Socket preservation at the time of extraction is one of the most significant procedures for future prosthetic considerations and for maintenance of the health. The most important aesthetic goals of socket preservation is maintenance or enhancement of the facial and interproximal gingival contours and height of the interproximal papilla thereby maintaining health, beauty and youth. This case report illustrates the use of epithelized connective tissue graft with an amalgamation of bone graft and doxycycline in socket preservation. Apart from this, platelet rich fibrin was used as a palatal bandage at the donor site to assess the wound healing. Socket preservation performed in left upper lateral incisor region with this tunnelling approach technique provided an optimum bone fill within the socket, thereby maintaining vertical bone height and stabilizing the marginal soft tissues at the desired site. The platelet rich fibrin used as a palatal bandage at the donor site aided in better wound healing at the graft procured site. Thus this technique can be used for obtaining a good bone volume, at the recipient site and may be applied in patients with thin gingival biotype.